Bioimpedance measurements of temporal changes in beating hearts. (16th December 2016) - Pettersen, F J; Martinsen, Ø G; Høgetveit, J O; Kalvøy, H; Odland, H H
Abstract: Electrical bioimpedance has been used over the years to measure various physiological parameters. Due to lack of high-speed instruments, there have been few options for making multi-frequency measurement series with high temporal resolution. This situation has changed lately, and with access to a commercially available impedance spectrometer, we have used this as part of an enhanced measurement set-up capable of measuring both bioimpedance and biopotentials with a temporal resolution in the millisecond-range. The set-up is controlled by a computer which also displays and processes the measurement data. Results from measurements in a human heart are shown. In these measurements, we can clearly see differences in the signal trajectory at current frequencies. The different trajectories indicate that with change in frequencies different physiological properties are reflected. We have shown that it is possible to detect changes in waveform morphology caused by a change in pacing modality. The ECG and EGM give additional information on global heart activity and electrical activity surrounding the electrodes. This measurement set-up allows us to further investigate bio-impedance as a measurement tool for rapid changes in impedance, such as in the cardiac field. The study was approved by the local institutional review boards (2014/1223/REK sør-øst A).